Pengaruh Pengetahuan Murid dan Pola Asuh Orang Tua terhadap Perilaku Jajan di SD Negeri 14 Meulaboh - Maizat, Maizat; Anwar, Sufyan; Rinawati, Rinawati; Muliadi, Teuku (Polyscopia, 2024)
This study aims to analyze the influence of students' knowledge and parental parenting styles on snacking behavior at SD Negeri 14 Meulaboh. The snacks available near the school are often unhygienic, exposed to dust and vehicle pollution, thereby posing health risks to students. This research employs a cross-sectional approach with quantitative methods, involving 69 student samples. Data were collected through questionnaires and analyzed using the Chi-Square statistical test. The results indicate a significant relationship between students' knowledge and snacking behavior (p=0.000), as well as between parental parenting styles and snacking behavior (p=0.003). These findings highlight the importance of educating both students and parents about healthy snack choices as a preventive measure to mitigate the adverse health impacts on children in the school environment.